Concepções e práticas de professores de ciências naturais sobre nutrição e saúde no ensino fundamental - Castro, Paula Morcelli de [UNIFESP] (2009)
Introduction: The teacher in the school environment, besides being an important model, is a potential ally to the knowledge construction on topics of nutrition area. Objective: Cognize the conceptions and practices of science teachers of elementary school about food and nutrition. Methodology: This is a transversal study with qualitative methodological strategy, realized in six elementary schools in Santos city, São Paulo. It was used a questionnaire to collect data where the information was filled by 4th and 5th years teachers. Results and Discussion: All participants of the survey n = 32 are female and aged between 26 and 67 years old, where 29 have higher education. Considering the teachers knowledge about food and nutrition, it was observed inappropriate concepts about food substitutes or equivalent. Beside, the interpretation of healthy feeding habits proved to be wrong, by using feeding restrictions. Among the teaching strategies used to approach the topic healthy eating in teaching practice, we found: reading and researches on the newspaper and magazines, didactic books, discussion, dialog, informal conversations, interviews, posters, panels, multi-media resources, computer laboratory, theater, personal experiences exchange. About the teachers experiences in the use of Information and Communication Technologies, their perceptions was that the virtual ambient can be an experience trade, representing a learning local of teachers formation enriching and helping the knowledge acquisition. Final considerations: Was observed in this study that some content about food and nutrition was proved wrong in teachers conceptions, reflecting the necessity of a formation process to them. And the pedagogical practices reported by the teachers was proved very diversified to show the theme. But, more researches are necessary, including other populations that may guide the process of teaching, for 4th and 5th years of environmental education in the knowledge construction about food and nutrition for students and teachers.